Nematicidal Assessment of Plant Mediated Green Synthesized Silver Nanoparticles Under Laboratory Conditions - Timi, David; Gopalakrishnan, Subramaniyam; Maino, Macquin (Transactions on Engineering and Computing Sciences, 2024)
Plant mediated biosynthesis of silver nanoparticles (AgNPs) and the bioactivity under laboratory condition on plant parasitic nematode, Meloidogyne incognita, is discussed. In the present study, aqueous extracts of the aerial parts of a medicinal weed, Euphorbia geniculata was utilized to construct AgNPs. The synthesized AgNPs was characterized by Ultraviolet-visible (UV-Vis.), Fourier Transform-infrared (FT-IR), X-ray Diffraction (XRD) spectrometer and Scanning Electron Microscopy (SEM) analysis. The species identification of M. incognita was accomplished via the DNA-PCR technique. The green biosynthesized AgNPs demonstrated comparable nematicidal activity with the reference chlorpyrifos against Meloidogyne incognita identified through DNA assay in PCR.